2008
DOI: 10.1634/stemcells.2007-0919
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Frequency and Distribution of Stem and Progenitor Cells in the Adult Mouse Brain

Abstract: The neurosphere assay can detect and expand neural stem cells (NSCs) and progenitor cells, but it cannot discriminate between these two populations. Given two assays have purported to overcome this shortfall, we performed a comparative analysis of the distribution and frequency of NSCs and progenitor cells detected in 400 m coronal segments along the ventricular neuraxis of the adult mouse brain using the neurosphere assay, the neural colony forming cell assay (N-CFCA), and label-retaining cell (LRC) approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 59 publications
2
79
2
Order By: Relevance
“…However, further studies are warranted to investigate whether the observed changes in dopaminergic neurogenesis translate into functional changes of the dopaminergic system in the postnatal and/or adult brain. Detailed knowledge of the composition of the midbrain neurogenic niche harboring dopaminergic NPC capacity will eventually help to develop restorative strategies for neurodegenerative diseases such as Parkinson's disease by both recruitment of endogenous progenitor cells from the niche [50][51][52] and improvement of dopaminergic cell graft. Our study, therefore, provides the initial framework for future studies on the molecular mechanisms mediating oxygen regulation of dopaminergic neurogenesis within the midbrain neurogenesis as its natural environment.…”
Section: /Nurr1mentioning
confidence: 99%
“…However, further studies are warranted to investigate whether the observed changes in dopaminergic neurogenesis translate into functional changes of the dopaminergic system in the postnatal and/or adult brain. Detailed knowledge of the composition of the midbrain neurogenic niche harboring dopaminergic NPC capacity will eventually help to develop restorative strategies for neurodegenerative diseases such as Parkinson's disease by both recruitment of endogenous progenitor cells from the niche [50][51][52] and improvement of dopaminergic cell graft. Our study, therefore, provides the initial framework for future studies on the molecular mechanisms mediating oxygen regulation of dopaminergic neurogenesis within the midbrain neurogenesis as its natural environment.…”
Section: /Nurr1mentioning
confidence: 99%
“…66,2009 Review Article tional data are still lacking [142]. In addition, markers of proliferation such as proliferating cell nuclear antigen (PCNA) and Ki67 are frequently used to label cells within the cell cycle; however, their association with NSCs has not been demonstrated, partially due to the lack of markers.…”
Section: Intrinsic Control Of Nscs and Neurogenesismentioning
confidence: 99%
“…Table S2). While other in vitro cultured multiaggregate spheroids were enriched in stem cells (i.e., less differentiated), this property would appear to be tissue-specific (including neural and mammary tissues), 63,64 as other sphere-forming cells actually demonstrate reduced differentiation capacity (i.e., reduced plasticity/stemness). 65,66 It is conceivable that our in vitro spheroids resemble those in the abovementioned melanoma differentiation studies.…”
mentioning
confidence: 99%